Activation of pentafluoropropane isomers at a nanoscopic aluminum chlorofluoride: hydrodefluorination versus dehydrofluorination - Kervarec, Maëva-Charlotte; Braun, Thomas; Ahrens, Mike; Kemnitz, Erhard (Beilstein Journal of Organic Chemistry, 2020)
The hydrofluorocarbon 245 isomers, 1,1,1,3,3-pentafluoropropane, 1,1,1,2,2- pentafluoropropane, and 1,1,1,2,3-pentafluoropropane (HFC-245fa, HFC-245cb, and HFC-245eb) were activated through C–F bond activations using aluminium chlorofluoride (ACF) as a catalyst. The addition of the hydrogen source Et3SiH is necessary for the activation of the secondary and tertiary C–F bonds. Multiple C–F bond activations such as hydrodefluorinations and dehydrofluorinations were observed, followed by hydroarylation and Friedel–Crafts-type reactions under mild conditions.
Keywords: aluminum fluoride; C–F bond activation; dehydrofluorination; hydrodefluorination; hydrofluorocarbons